1960
DOI: 10.1172/jci104093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Anterior Pituitary in the Control of Aldosterone Secretion in Experimental Secondary Hyperaldosteronism*

Abstract: Previous reports (1-9) have delegated a secondary role to anterior pituitary hormones in the control of aldosterone secretion.' Although hypophysectomy resulted in decreased aldosterone secretion (3) or reduced urinary aldosterone output (2), hyperaldosteronuria, marked sodium (Na) retention and ascites occurred in the absence of the adenohypophysis in dogs with thoracic inferior vena cava constriction (2). Also, in patients with hypopituitarism, Luetscher and Axelrad (6) and Hernando and associates (7) found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
3

Year Published

1961
1961
1970
1970

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 30 publications
1
18
3
Order By: Relevance
“…Our results indicate that aldosterone values may be essentially unchanged the day after hypophysectomy. Davis and his colleagues did indeed find low rates of aldosterone secretion in dogs with hypophysectomy of long standing which had been deprived of sodium after hypophysectomy (7). In another experiment however, in which dogs were hypophysectomized after sodium depletion had been produced (by dietary sodium deprivation and injections of Mercuhydrin), the rate of aldosterone secretion was high (32).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results indicate that aldosterone values may be essentially unchanged the day after hypophysectomy. Davis and his colleagues did indeed find low rates of aldosterone secretion in dogs with hypophysectomy of long standing which had been deprived of sodium after hypophysectomy (7). In another experiment however, in which dogs were hypophysectomized after sodium depletion had been produced (by dietary sodium deprivation and injections of Mercuhydrin), the rate of aldosterone secretion was high (32).…”
Section: Discussionmentioning
confidence: 96%
“…This is based on morphological studies in the rat (1), on indirect assessments of adrenal secretion during metabolic studies in man (2), and on direct estimations of adrenal hormone secretion in the rat (3,4) and dog (5)(6)(7). The morphological studies of Deane and Masson (8), which indicate that renin may stimulate the adrenal cortex in the rat, the results of Genest and his colleagues (9), which suggest that arterial hypertension may be associated with an increased excretion of aldosterone in man, and the demonstration by Genest ( 10,11 ) and Laragh (12) and their colleagues that angiotensin II stimulates excretion (10,11) and secretion (12,13) of aldosterone suggest that the kidney may have some influence on the rate of secretion of adrenal hormones.…”
mentioning
confidence: 99%
“…Initial studies indicated that ACTH was not important in the control of aldosterone secretion (37,38). Subsequent studies have demonstrated that whereas aldosterone is still secreted in the absence of ACTH, secretion and responsiveness to alterations in the activity of the renin-angiotensin system is diminished (39)(40)(41).…”
Section: Isolation and Quantitation Of Aldosterone And 18-hydroxycortmentioning
confidence: 99%
“…Possible reasons for the continuance of aldosterone hypersecretion in these experiments are: 1) ACTH. In sufficiently high doses ACTH stimulates aldosterone secretion directly (2,(6)(7)(8).…”
Section: Chemical Proceduresmentioning
confidence: 99%
“…Crosscirculation studies of Denton, Goding, and Wright (1) and Yankopoulos, Davis, Kliman, and Peterson (5) indicate that the stimulus to the adrenal is humoral. Three local humoral circumstances, ACTH infusion (2,(6)(7)(8), angiotensin II infusion (2,6,(9)(10)(11)(12), and low sodium and high potassium concentration of plasma (1,2,6,13), are known to cause an increase in aldosterone secretion, and the levels required for the reaction are not beyond those that are known or might be presumed to occur naturally. However, conscious unstressed dogs with thoracic caval constriction showed a 20-to 40-fold increase in aldosterone secretion rates associated with low corticosterone and Porter-Silber chromogen secretion (14).…”
mentioning
confidence: 99%